Patient-associated mutations in Drosophila Alk perturb neuronal differentiation and promote survival. - Pfeifer, K.; Wolfstetter, G.; Anthonydhason, V.; Masudi, T.; Arefin, B.; Bemark, M.; Mendoza-Garcia, P.; Palmer, R.H. (Disease models & mechanisms, 2022)
Activating anaplastic lymphoma kinase (ALK) receptor tyrosine kinase (RTK) mutations occur in pediatric neuroblastoma and are associated with poor prognosis. To study ALK-activating mutations in a genetically controllable system, we employed CRIPSR/Cas9, incorporating orthologs of the human oncogenic mutations ALKF1174L and ALKY1278S in the Drosophila Alk locus. AlkF1251L and AlkY1355S mutant Drosophila exhibited enhanced Alk signaling phenotypes, but unexpectedly depended on the Jelly belly (Jeb) ligand for activation. Both AlkF1251L and AlkY1355S mutant larval brains displayed hyperplasia, represented by increased numbers of Alk-positive neurons. Despite this hyperplasic phenotype, no brain tumors were observed in mutant animals. We showed that hyperplasia in Alk mutants was not caused by significantly increased rates of proliferation, but rather by decreased levels of apoptosis in the larval brain. Using single-cell RNA sequencing, we identified perturbations during temporal fate specification in AlkY1355S mutant mushroom body lineages. These findings shed light on the role of Alk in neurodevelopmental processes and highlight the potential of Alk-activating mutations to perturb specification and promote survival in neuronal lineages. This article has an associated First Person interview with the first author of the paper.